Strategi Pembelajaran PAI Dalam Penerapan Pendidikan Multikultural Di SMP Negeri 1 Gudo - Jalil, Abdul; Munif, Achmad Abdul (LP3M STIT Al Urwatul Wutsqo Jombang, 2022)
Islam is a religion that we adhere to and adhere to by hundreds of millions of Muslims in all corners of the world, which is a source of aspects of life that guarantee the happiness of its adherents both in this world and in the hereafter. The PAI teacher's strategy in PAI learning is to start with determining the right PAI learning material involving Muslim students such as muamalah (social relations) material by choosing the right method such as lectures, discussions, and questions and answers so that no debate has an impact on disputes between Muslim students and non-Muslim students. non-muslim. Then also the use of appropriate and efficient media so that the audio-visual media used by the teacher can accommodate a short time, namely three hours of lessons for one week. The reasons for PAI learning in the application of multicultural education are applied by PAI teachers at SMPN 1 Gudo, among others: students at the school have various ethnic, racial, and religious backgrounds; there are no other religious teachers in the school except PAI teachers; some non-Muslim students have a desire to participate in PAI learning, especially in muamalah (social relations), because the author is interested in researching PAI learning strategies in the application of multicultural education and evaluation steps in PAI learning at SMPN 1 Gudo. The purpose of this study is the application of multicultural education because it has diverse ethnic, racial, and religious backgrounds and the absence of non-Muslim religious teachers has an impact on the non-participation of students in learning when PAI learning takes place